Amelioration of colitis through blocking lymphocytes entry to Peyer's patches by sphingosine‐1‐phosphate lyase inhibitor. Issue 9 (12th March 2018) - Shirakabe, Kazuhiko; Higashiyama, Masaaki; Furuhashi, Hirotaka; Takajo, Takeshi; Maruta, Koji; Okada, Yoshikiyo; Kurihara, Chie; Watanabe, Chikako; Komoto, Shunsuke; Tomita, Kengo; Nagao, Shigeaki; Miura, Soichiro; et al.
Abstract: Background and Aim: Sphingosine‐1‐phosphate (S1P) receptor 1, a therapeutic target of the S1P1 agonist FTY720, plays a crucial role in lymphocyte migration and is expressed in several cells including naïve T lymphocytes and endothelial cells. 2‐Acetyl‐4‐tetrahydroxybutyl imidazole (THI), an inhibitor of S1P lyase, exhibits immunomodulatory activity through increasing the S1P concentration in the secondary lymphoid organs, but its effects on colitis remain unclear. This study aimed to clarify how THI affects colitis and migration of naïve T lymphocytes in Peyer's patches (PPs). Methods: The effect of THI on gut immunity was investigated by analyzing the dextran sulfate sodium (DSS)‐induced murine colitis model, lymphocyte components in thoracic duct lymphocytes (TDLs), and microscopic movement of TDLs in PPs. Results: 2‐Acetyl‐4‐tetrahydroxybutyl imidazole ameliorated DSS‐induced colitis histologically by causing a significant decrease in colonic lymphocyte infiltration and expression of mucosal pro‐inflammatory cytokines. THI suppressed the inflow of naïve T lymphocytes into the thoracic duct. Microscopic observation of PPs in control animals revealed that many TDLs egressed to the stroma and migrated to lymph capillaries after attaching to the high endothelial venules (HEVs). THI or FTY720 treatment in recipient animals blocked lymphocyte egression from the HEVs to the stroma. Conclusions: This is the first study to clarify the ameliorating effects of THI on DSS‐induced colitis. Microscopic observations demonstrated the involvement of HEVs in the egression of S1P‐dependent gut‐tropic T lymphocytes to lymph capillaries. This S1P lyase inhibitor might become a novel immunosuppressant for inflammatory bowel disease therapy by blocking infiltration of lymphocytes through HEVs into the stroma in PPs.